Avaliação do impacto da implantação da Universidade Federal do Pampa sobre os indicadores da educação básica no município de Bagé - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The present work analyzed, through a public policy impact assessment, the impact of the implementation of the Federal University of Pampa – Unipampa, on the indicators of basic education in the city of Bagé/RS. The method used was the case study, the quantitative approach and the period of analysis between 2007 and 2019. The evaluation consisted of the application of the difference-in-differences technique comparing the evolution of basic education indicators in Bagé/RS, with the evolution of a previously constructed control group with municipalities with similar characteristics. The results pointed to the absorption of 137 professionals in the basic education network of Bagé/RS, and to a greater capacity of the High School network to absorb these professionals. The observed impacts are related to the increase in the Yield Rate and the reduction in the Abandonment Rate, both statistically significant, related to the implementation of public policy and aligned with the established logical model.
Keywords: Política pública - Avaliação; Educação básica - Bagé (RS); Universidades e faculdades; Universidade Federal do Pampa; Public policy – Evaluation; Basic education - Bagé (RS); CNPQ::CIENCIAS HUMANAS